2018
DOI: 10.1186/s12864-018-4584-2
|View full text |Cite
|
Sign up to set email alerts
|

Lowered dietary phosphorus affects intestinal and renal gene expression to maintain mineral homeostasis with immunomodulatory implications in weaned piglets

Abstract: BackgroundIn monogastric animals, phosphorus (P) homeostasis is maintained by regulating intestinal absorption, bone mobilization, and renal excretion. Since P is a non-renewable resource, a shortage is imminent due to widespread over-usage in the farming and animal husbandry industries. As a consequence, P efficiency should be improved in pig production. We sought to characterize the transcriptional response in re−/absorbing and excreting tissues in pigs to diets varying in calcium: phosphorus ratios. Weaned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 70 publications
1
13
1
Order By: Relevance
“…Moreover, the P homeostasis also depends on several sometimes contradictory factors such as regulators, transporters, and endocrine and paracrine signals whose endocrine function and integration into networks have not yet been clearly identified [20][21][22][23][24][25][26]. Consequently, the mechanisms that mediate P homeostasis contribute to a significant phenotypical variation [27,28]. Accordingly, one important step to improve P efficiency and reduce P excretion is a finely graduated phase feeding or precision feeding regimen which is already used to a certain extent to adapt growth performance to ontogenetic requirements.…”
Section: Feeding Regimenmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the P homeostasis also depends on several sometimes contradictory factors such as regulators, transporters, and endocrine and paracrine signals whose endocrine function and integration into networks have not yet been clearly identified [20][21][22][23][24][25][26]. Consequently, the mechanisms that mediate P homeostasis contribute to a significant phenotypical variation [27,28]. Accordingly, one important step to improve P efficiency and reduce P excretion is a finely graduated phase feeding or precision feeding regimen which is already used to a certain extent to adapt growth performance to ontogenetic requirements.…”
Section: Feeding Regimenmentioning
confidence: 99%
“…Few studies with holistic approaches have focused on molecular metabolic pathways that are relevant for reduced and excessive P supply in farm animals [28,52]. Experiments elucidating the genotype-phenotype map will likely prove beneficial for the characterization of the molecular mechanisms of P efficiency.…”
Section: Feeding Regimenmentioning
confidence: 99%
See 1 more Smart Citation
“…Although one animal from the low PU group showed some uncertainty, successful discrimination of PU divergent animals based on ileal gene expression underlines the relevance of the intestinal capacity and the involvement of host genetic factors in the population-wide variability of PU as previously indicated by heritability estimates for this trait [5]. Accordingly, studies in non-avian monogastric species such as pigs revealed a gene-environment interaction in relation to P homeostasis [2,8,17]. Using the ileal DEGs, a functional enrichment analysis was performed to further clarify the underlying mechanisms and the intestinal contribution to PU.…”
Section: Sequencing Data Analysis and Differential Gene Expressionmentioning
confidence: 75%
“…Due to physiological turn-over and growth processes, the dynamics of P absorption, P storage, and P excretion are of particular importance to maintain animal health and growth performance. The resulting interaction of tissues such as small intestine, bones, and kidneys prompt an individual physiological release of hormones [1], tissue-specific downstream signaling events [2], and modified bone mineralization [3] to account for varying environmental conditions. With respect to P, physiologic adaptations imply effects on gastrointestinal processes, intermediate metabolism, and mechanisms of resource allocation, which all affect the efficiency of P utilization (PU) of the animal.…”
Section: Introductionmentioning
confidence: 99%